2000
DOI: 10.1038/sj.jea.7500138
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PM2.5 and PM10 monitors

Abstract: An extensive PM monitoring study was conducted during the 1998 Baltimore PM Epidemiology -Exposure Study of the Elderly. One goal was to investigate the mass concentration comparability between various monitoring instrumentation located across residential indoor, residential outdoor, and ambient sites. Filter -based ( 24 -h integrated ) samplers included Federal Reference Method Monitors ( PM 2.5 -FRMs ) , Personal Environmental Monitors ( PEMs ) , Versatile Air Pollution Samplers ( VAPS ) , and cyclone -based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 7 publications
3
19
1
Order By: Relevance
“…This finding is unusual; of eleven recent studies, most showed mean personal exposures that were higher than mean outdoor concentrations (personal/outdoor ratios ranging from 0.8 to 2.5, compared to our ratio of 0.6, the lowest of all the studies) (Jannsen et al 1999;Pellizzari et al 1999;2001;Rojas-Bracho et al 2000;Williams et al 2000;Weisel et al 2005;Turpin et al 2007;Brown et al 2008). The DEARS study in the neighboring city of Detroit took place in the same years and resulted in similar mean outdoor PM 2.5 concentrations of about 16 µg/m 3 (Williams et al 2008), which is nearly identical to the mean of 15.9 µg/m 3 in Windsor; yet the mean indoor concentrations in Detroit were 19 µg/m 3 compared with 8 µg/m 3 in Windsor.…”
Section: Discussioncontrasting
confidence: 38%
“…This finding is unusual; of eleven recent studies, most showed mean personal exposures that were higher than mean outdoor concentrations (personal/outdoor ratios ranging from 0.8 to 2.5, compared to our ratio of 0.6, the lowest of all the studies) (Jannsen et al 1999;Pellizzari et al 1999;2001;Rojas-Bracho et al 2000;Williams et al 2000;Weisel et al 2005;Turpin et al 2007;Brown et al 2008). The DEARS study in the neighboring city of Detroit took place in the same years and resulted in similar mean outdoor PM 2.5 concentrations of about 16 µg/m 3 (Williams et al 2008), which is nearly identical to the mean of 15.9 µg/m 3 in Windsor; yet the mean indoor concentrations in Detroit were 19 µg/m 3 compared with 8 µg/m 3 in Windsor.…”
Section: Discussioncontrasting
confidence: 38%
“…164 PM 2.5 mass from the dichotomous sampler was approximately 17% lower than MOUDI in Los Angeles, 165 attributed to NO 3 Ϫ volatilization. At a low flow rate (2 L/min), Williams et al 166 showed that a PM 2.5 personal environmental monitor (PEM; MSP, Inc.) used for exposure assessments 167-169 measured 16 -18% higher mass than a collocated FRM. Table 12 shows that various FRM measurements were within 10% of each other, whereas FRM was within Ϯ10 -20% of non-FRM PM 2.5 mass.…”
Section: Oc and Ecmentioning
confidence: 99%
“…The detailed site information can be found in Figs. 1 Price et al (2003), and Williams et al (2000). Reference methods for PM 10 and PM 2.5 mass concentrations includes the European reference method (EN 12341 NORM) and the US EPA reference method for PM 10 (http://www.epa.gov/ttn/emc/promgate/m-201.pdf).…”
Section: Pm 10 Data Over Canadamentioning
confidence: 99%